The Educational Thoughts of John Dewey and Sri Aurobindo: Exploring the Impact of John Dewey and Sri Aurobindo on Education (Journal of Advances and Scholarly Researches in Allied Education, 2015)
To fulfill the aspects of education such as in beauty, power, knowledge and love by integrating all of them through integral education that bring out the full advantage in each individual child and draw out the best that is within and make it perfect for a noble causes. In the said research, a study of thoughts of Sri Aurobindowas conducted. This paper discusses the influence of John Dewey’s educational thoughts on Education in the past and in the present. It also elaborates the manifestations of the Deweyan vision of a democratic and pro-gressive education.